Fruit trees pollinated by bees in Brazil - Modro, Anna Frida Hatsue; D’Avila, Márcia; Marchini , Luis Carlos (SITIENTIBUS série Ciências Biológicas, 2010)
In several agricultural crops, entomophilous pollination is one of the factors contributing to yield increase. Lack of native pollinators allowed directed pollination with bees to become an important tool in agricultural production, although evaluation of its efficiency in some cultures still needs further study. This work aimed to collect information on pollination with bees in acerola, cashew, citrus, apple, passion fruit, melon and strawberry fruit trees in Brazil.